Behavior Analysis of Covid-19 Prevention in Community of Productive Age in the City of Palembang - Sintia Arlina; Nur Alam Fajar; Yuanita Windusari (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Reported cases of Covid-19 were found in 203 countries around the world in early April 2020, Indonesia showed a large number of confirmed cases and deaths in the Covid-19 outbreak. The first known case of Covid-19 in Palembang occurred in March 2020. Covid-19 continues to spread to all areas in South Sumatra, including the city of Palembang. In the grouping of the population based on age and ability, there are two groupings, namely, the non-productive population group and the productive age group. The productive age group is the population aged between 19-60 years. The productive age group is the largest population who plays an important role. Therefore, people at productive age do the most activities so that good behavior is needed to comply with the implementation of health protocols. This research was conducted to find out how the description of knowledge, attitudes and behavior of the people of Palembang City in preventing Covid-19. This research is important to do to find out the next strategic steps that can be done through community empowerment. The method used in this study uses quantitative methods. Respondents in this study amounted to 119 people of productive age in the city of Palembang. Based on the results of the research conducted, the results obtained in the form of characteristics of people of productive age based on age, gender, last education, occupation and length of working hours, knowledge of productive age people's behavior and attitudes towards productive age people's behavior. The results obtained from this study show that there is a relationship between knowledge of the behavior of people of productive age regarding Covid-19 who get a p-value of 0.003, there is a relationship between attitudes towards the behavior of people of productive age regarding Covid-19 with a p-value of 0.000 and the presence of the relationship between behavior towards Covid-19 preventive behavior with a p-value of 0.000. The conclusion in this study is that there is no relationship between the characteristics of respondents of productive age that affect the behavior of preventing Covid-19 in Palembang City, but knowledge of Covid-19 prevention, Covid-19 prevention attitudes and community prevention behavior in suppressing the number of Covid-19 in the city of Palembang very influential.